2017
DOI: 10.15406/mojsm.2017.01.00027
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Swimming, Cycling and Running in the Final Performance in Different Distances of Triathlon Races

Abstract: The aim of the study was to analyze which modality (swimming, cycling or running) may interfere significantly to the final performance of different triathlon events. The present study observed the last five results of Olympic Distance, Half Distance and Full Distance (Ironman) of World Championship from 2010 to 2015. The athlete's times were tabulated separate per: swimming time, cycling time, running time and total time. The sample was divided in two groups: (G1) athletes who were classified among the five be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…The first important finding was that swimming was the better predictor for overall performance in Olympic-distance triathlon. Swimming was the discipline representing the smallest portion in all triathlon distances ( Scorcine et al, 2017 ), but its importance was different depending on the triathlon event. In draft-legal triathlons (i.e., Sprint and Olympic), a slow swim may result in a slower peloton or a lonely cycling portion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first important finding was that swimming was the better predictor for overall performance in Olympic-distance triathlon. Swimming was the discipline representing the smallest portion in all triathlon distances ( Scorcine et al, 2017 ), but its importance was different depending on the triathlon event. In draft-legal triathlons (i.e., Sprint and Olympic), a slow swim may result in a slower peloton or a lonely cycling portion.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of a given discipline across various distances and importance to predict overall performance can help coaches, and athletes tailor specific goals for a specific event ( Figueiredo et al, 2016 ). It has been shown that the split disciplines contribute differently to overall race performance regarding the length of a triathlon race ( Figueiredo et al, 2016 ; Scorcine et al, 2017 ). It has been shown that running was the most predictive split discipline in Olympic-distance triathlon ( Gadelha et al, 2020 ), whereas cycling was the most predictive in IM distance triathlon ( Sousa et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several race distances are recognized, such as Sprint distance, Olympic distance, Half distance, and Full distance (Table 1 ). Moreover, the Mixed-team relay is a new short race event during which four athletes (in the order female–male–female–male) complete a super-sprint triathlon [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The duration of a race can last 15–20 min for the Mixed-team relay up to 7–12 h for the Full-distance triathlon, while elite Olympic distance athletes can finish a competition in less than 2 h. Triathlon cannot be considered a single performance but as a sequence of the three different disciplines, hence each segment can influence the subsequent one and the overall performance [ 3 ], especially for World Triathlon Series (WTS) shorter distance events (i.e., Mixed-team relay, Sprint distance, and Olympic distance) [ 2 ]. Generally, the contribution of each segment to the total time is up to 20% for swimming, between 50 and 60% for cycling, and 30–40% for running [ 2 ]. Although the swim segment is the shortest distance of the race, swimming could have a substantial influence on the final result in Olympic distance [ 2 , 4 ], as it has been observed that 90% of male and 70% of female winners exit the water in the first pack [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation